Hotel selection attributes and booking intention: Challenges of hotel industry in the oost COVID-19 pandemic era - I Gusti Agung Gede Witarsana; Ida Bagus Putu Puja; Putu Diah Sastri Pitanatri; Sachriani; Saiful Ghozi (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to investigate the influence of hotel selection attributes, CHSE (clean, health, safety, and environment) practice, and brand credibility on hotel booking intention. Additionally, this study investigates the role of CHSE practices, together with brand credibility, as moderating factors in the relationship between hotel selection attributes and hotel booking intention among travelers. Design/methodology/approach: With an incidental sampling technique, in the aftermath of the COVID-19 pan- demic, data were collected from 157 travellers over 20 years old who had stayed in a CHSE-certified hotel in Bali, Indonesia. Partial least squares structural equation modelling was utilized to assess the relationship model. Findings: This study reveals that hotel selection attributes, CHSE practice, and brand credibility positively influence on hotel booking intention. CHSE practice weakens the positive influence of hotel selection attributes on booking intention. While brand credibility reinforces the said influence. In the framework of signaling theory, CHSE practice can be seen as an internal signal that can influence hotel booking intention. While brand credibility is an external signal. Research limitations/implications: This finding cannot be generalized to other contexts and countries. Another limitation is that respondents filled out the questionnaire when they were not on the spot of the hotel due to potential disturbing leisure and location permit constraints. Future studies could pay attention to collecting data while the respondent is still at the hotel to obtain more updated questionnaire responses. The outcome of this study has practical implications for hotel management in designing strategic plans to improve hotel booking intentions. Originality/value: This study contributes to the literature on the moderating variable in the positive influence of travellers' hotel selection attributes on booking intention, which has never been explored before. In actuality, the post-COVID-19 pandemic will never be identical to the pandemic period, especially in terms of how travellers make considerations when booking hotels.
Keywords: 650; Hotel selection attributes; CHSE practice; Brand credibility; Booking intention; Post COVID-19 pandemic era